EFEKTIVITAS EKSTRAK KAPANG ENDOFIT ISOLAT BR-S1 (A) TERHADAP BAKTERI Methicillin-Resistant Staphylococcus aureus (MRSA) - Kurniawan kurniawan kurniawan; Nuniek Ina Ratnaningtyas (Meditory : The Journal of Medical Laboratory, 2018)
Background Tea parasitic plant (Scurrula oortiana L.) is one of medicinal plants (herba medicina) containing several active compounds but its utilization is still constrained by some problems, so that there needs other approaches by utilizing potential of BR-S1 (A) isolate endophytic fungi which grows in these plants to control MRSA pathogenic bacteria. Objective This research aimed to examine the effectiveness of the four types of BR-S1 (A) endophytic fungi extract  from the origin of tea parasites to the growth of MRSA bacteria.Methods The researchers used laboratory experimental method by Kirby Bauer disk diffusion method and the data obtained were analyzed statistically. Result The research result showed that MRSA bacteria had various sensitivity on four types of BR-S1 (A) isolate endophytic fungi; with its highest sensitivity on extract of ethyl acetate and its lowest sensitivity was extract of n-hexane (no inhibition). The difference of sensitivity test results was suspected to be related to active compound content found in ethyl acetate extract in form of flavonoid and tannin class compounds which had been proven to inhibit growth of pathogenic bacteria.  Conclusion It can be concluded that  the four types of BR-S1 (A) endophytic fungus extract originating from tea parasites, only ethyl acetate extract was the most effective in inhibiting the growth of MRSA bacteria, this is due to the content of two active compounds from the flavonoid and tannin groups.